Comparison of ozone retrievals from the Pandora spectrometer system and Dobson spectrophotometer in Boulder, Colorado - J. Herman; R. Evans; A. Cede; N. Abuhassan; I. Petropavlovskikh; G. McConville (Atmospheric Measurement Techniques, 2015)
A comparison of retrieved total column ozone (TCO) amounts between the Pandora #34 spectrometer system and the Dobson #061 spectrophotometer from direct-sun observations was performed on the roof of the Boulder, Colorado, NOAA building. This paper, part of an ongoing study, covers a 1-year period starting on 17 December 2013. Both the standard Dobson and Pandora TCO retrievals required a correction, TCOcorr = TCO (1 + C(T)), using a monthly varying effective ozone temperature, TE, derived from a temperature and ozone profile climatology. The correction is used to remove a seasonal difference caused by using a fixed temperature in each retrieval algorithm. The respective corrections C(TE) are CPandora = 0.00333(TE-225) and CDobson = -0.0013(TE-226.7) per degree K. After the applied corrections removed most of the seasonal retrieval dependence on ozone temperature, TCO agreement between the instruments was within 1 % for clear-sky conditions. For clear-sky observations, both co-located instruments tracked the day-to-day variation in total column ozone amounts with a correlation of r2 = 0.97 and an average offset of 1.1 ± 5.8 DU. In addition, the Pandora TCO data showed 0.3 % annual average agreement with satellite overpass data from AURA/OMI (Ozone Monitoring Instrument) and 1 % annual average offset with Suomi-NPP/OMPS (Suomi National Polar-orbiting Partnership, the nadir viewing portion of the Ozone Mapper Profiler Suite).